Mental Health in Later Life : Taking a Life Course Approach - Milne, Alisoun (Book collections on Project MUSE., 2020)
Focusing on mental health rather than mental illness, this book adopts a lifecourse approach to understanding mental health and wellbeing in later life. Well-respected author and scholar Alisoun Milne explores the influences of lifecourse experiences, structural inequalities, socio-political context, history, gender and age related factors and engages with new ways of thinking about preventing mental ill health and promoting mental health in later life. Drawing together material from a number of different fields, the book analyses the meaning and determinants of mental health among older populations and offers a critical review of the lifecourse, ageing and mental health discourse for students, professionals, policy makers and researchers.